"مـفارقـة البنـية السردية في خـفايا وأسرار الماضي لرواية"حوبة ورحلة البحث عن المهدي المنتظر" لعز الدين جلاوجي. - عاشور, شفيقة (Revues faculté des lettres et des langues, 2018)
Abstract: The narrative period has given a great importance thanks to the interest of a great number of philosophers and critics. They have participated in the ellucidation of its features ‘’Gerard Genette’’ was able to clarify the problem of time and show how to deal with it in the narrative side though his work ‘’ speech of story’’ . He has started through his point of view that says that the time of any novel is not real it does not reflect the real time of the novel. We approach through this study to limit the level of chronological classification in the novel ‘’ Hoba’’ , we do not claim familarity with all the sides that include this later , but we are just dealing with the important sides that the algerian creator’’ Azzdine Djlaoudji’’ has dealt with in his book creativity. الملخص حظي الزمن السردي باهتمام كبير من النقاد والفلاسفة، إذ أسهموا في استجلاء معالمه وتوضيحها، فاستطاع "جيرار جنيت" من خلال منجزه" خطاب الحكاية" أن يترجم الجهود المشتغلة على قضية الزمن وكيفية التعامل معه في الجانب الروائي، مبتدءا بنظرته القائلة بأن زمن الرواية زمن مزيف لا يعكس الزمن الحقيقي للمادة القصصية الفعلية، فنسعى من خلال هذه الدراسة إلى تحديد مستوى الترتيب الزمني في رواية "حوبة"، ولا ندعي الإلمام بكامل الجوانب التي يكتنفها هذا الأخير، فحسبنا فقط أن نتناول الجوانب المهمة التي استند إليها المبدع الجزائري " عزالدين جلاوجي" في كتابته الإبداعية.